Use of Plasma Renin Activity to Monitor Mineralocorticoid Treatment in Dogs with Primary Hypoadrenocorticism: Desoxycorticosterone Versus Fludrocortisone. (September 2014) - Baumstark, M.E.; Nussberger, J.; Boretti, F.S.; Baumstark, M.W.; Riond, B.; Reusch, C.E.; Sieber‐Ruckstuhl, N.S.
<x xml:space="preserve">Abstract</x> Background Measurement of plasma renin activity (PRA) is the gold standard for monitoring mineralocorticoid treatment in humans with primary hypoadrenocorticism (PH). Objectives To compare PRA in dogs with newly diagnosed PH, dogs with diseases mimicking PH, and healthy dogs, and evaluate measurement of PRA to monitor therapeutic effects in dogs with PH treated with different mineralocorticoids. Animals Eleven dogs with newly diagnosed PH (group 1), 10 dogs with diseases mimicking PH (group 2), 21 healthy dogs (group 3), 17 dogs with treated PH (group 4). Methods In group 1, PRA was measured before treatment and at different times after initiating treatment. In groups 2 and 3, PRA was measured at initial presentation only. In group 4, no baseline PRA was obtained but PRA was measured once or every 1–6 months during treatment. Mineralocorticoid treatment consisted of fludrocortisone acetate (FC) or desoxycorticosterone pivalate (DOCP). Results Plasma renin activity before treatment was increased in dogs with PH compared to normal dogs and dogs with diseases mimicking PH with median activity of 27, 0.8, and 1.0 ng/mL/h, respectively. In dogs with PH, PRA decreased and normalized with mineralocorticoid treatment using DOCP but not with FC. In dogs treated with DOCP, PRA was lower than in dogs treated with FC. Plasma sodium concentrations were higher and potassium concentrations were lower with DOCP treatment compared to FC treatment. Conclusion and Clinical Importance Plasma renin activity is a reliable tool for monitoring mineralocorticoid treatment. DOCP treatment more effectively suppresses PRA compared to FC in dogs with PH.